Clinical characteristics of patients with obstructive coronary lesions in the absence of coronary calcification: an evaluation by coronary CT angiography. Issue 13 (22nd April 2009) - Marwan, M; Ropers, D; Pflederer, T; Daniel, W G; Achenbach, S
Abstract : Background: Multidetector CT allows detection of coronary artery calcium and, after contrast injection, visualisation of the coronary artery lumen. It is commonly assumed that the absence of coronary calcification makes the presence of obstructive coronary lesions highly unlikely. This study evaluates the clinical characteristics of patients with at least one symptomatic, high-grade coronary artery stenosis in both computed tomography and invasive angiography but absence of any coronary calcification and compares the results with patients with stenoses in the setting of detectable coronary calcium Patients and methods: The study retrospectively identified 21 consecutive patients with symptoms in whom a high-grade coronary artery stenosis had been identified in 64-slice or dual-source CT coronary angiography (Siemens Sensation 64 or Siemens Definition, 120 kV, 50 to 85 ml of intravenous contrast at 5 ml/s) in the absence of coronary calcium and in whom that finding had been confirmed by invasive coronary angiography. Clinical presentation ("unstable": all forms of acute coronary syndrome versus "stable": stable chest pain or dyspnoea on exertion) and standard cardiovascular risk factors were assessed, and the results were compared with 42 consecutive patients with symptoms in whom both coronary calcium and coronary stenoses had been identified in computed tomography and invasive coronary angiography. Results: The majority of patients with coronary stenoses in the absence of coronary calcium presented with "unstable" symptoms (non-ST-segment elevation myocardial infarction (NSTEMI) or unstable angina), significantly more frequently than patients with detectable calcification (71% vs 26%, p = 0.001). The age range of patients without calcium was 33 to 76 years, their mean age was younger (53 (SD 13) vs 63 (8) years, p<0.001), but none of the risk factors showed any significant difference compared with patients with calcification. Conclusion: The presence of significant coronary artery stenosis in the absence of coronary calcium is possible. It is more likely in the setting of unstable angina or NSTEMI than in stable chest pain and occurs more frequently in younger patients.